Microbiological quality of drinking water of urban and rural communities, Brazil - Giovani Nogueira; Celso V Nakamura; Maria CB Tognim; Benício A Abreu Filho; Benedito P Dias Filho
OBJECTIVE: To evaluate the microbiological quality of treated and untreated water samples came from urban and rural communities and to examine the relationship between coliforms occurrence and average water temperature, and a comparison of the rainfall levels. METHODS: A sample of 3,073 untreated and treated (chlorinated) water from taps (1,594), reservoir used to store treated water (1,033), spring water (96) and private well (350) collected for routine testing between 1996 and 1999 was analyzed by the multiple dilution tube methods used to detect the most probable number of total and fecal coliforms. These samples were obtained in the region of Maringá, state of Paraná, Brazil. RESULTS: The highest numbers water samples contaminated by TC (83%) and FC (48%) were found in the untreated water. TC and FC in samples taken from reservoirs used to store treated water was higher than that from taps midway along distribution lines. Among the treated water samples examined, coliform bacteria were found in 171 of the 1,033 sampling reservoirs. CONCLUSIONS: Insufficient treatment or regrowth is suggested by the observation that more than 17% of these treated potable water contained coliform. TC and FC positive samples appear to be similar and seasonally influenced in treated water. Two different periods must be considered for the occurrence of both TC and FC positive samples: (i) a warm-weather period (September-March) with high percentage of contaminated samples; and (ii) cold-weather period (April-August) were they are lower. Both TC and TF positive samples declined with the decreased of water temperature.